Comparative characterization and phylogenetic analysis of complete mitogenome of three taxonomic confused groupers and the insight to the novel gene tandem duplication in Epinephelus - He, Haobin; Gao, Zihan; Hu, Zehua; Cai, Linhao; Huang, Yanhua; Zhou, Meng; Liang, Rishen (Frontiers in Marine Science, 2024)
Epinephelus bilobatus, Epinephelus maculatus and Epinephelus longispinis are three groupers that share common morphological characteristics and colouration patterns and have been morphologically confused and misidentified with each other for a long time. Complete mitochondrial genomes of the three groupers were determined and analysed in this study. Mitogenomes of E. bilobatus, E. maculatus and E. longispinis were 17, 354 bp, 17, 066 bp and 17, 221 bp in size respectively and consisted of 13 protein-coding genes, two ribosomal RNA genes and one control region. However, different from most teleosts, which contain canonical 22 tRNAs, more numbers of tRNAs were identified in the three groupers with 27 tRNAs in E. bilobatus and E. longispinis and 25 tRNAs in E. maculatus. The increased number of tRNAs was due to the presence of tandemly duplicated tRNA-Asp genes that were located between tRNA-Ser and COII genes (six duplications in E. bilobatus and E. longispinis, four duplications in E. maculatus). Intact gene tandem duplication was an uncommon feature that was found in the typical teleost mitogenomes. The phylogenetic trees of the 32 groupers (genus Epinephelus) that were constructed based on 12 protein-coding genes revealed that Epinephelus species with tandemly duplicated tRNA-Asp genes were clustered into one monophyletic group, distinct from other Epinephelus species without any duplication features, which indicated that tandemly duplicated tRNA-Asp genes may be the particular linage-specific characteristics that evolve from a common ancestor and have the ability to distinguish them from other Epinephelus species. The results of the mitogenomes comparative analyses of the three groupers revealed the genetic distance of mitogenomes between each two species to be 0.062 (E. bilobatus vs E. maculatus), 0.091 (E. bilobatus vs E. longispinis) and 0.087 (E. maculatus vs E. longispinis). All values were far greater than the minimum value of 0.020 for species identification, which shows that they were three